ENVIRONMENTAL SUSTAINABILITY AND ECONOMY - SINGH PRADEEP; PRAMIT VERMA; DANIELA PERROTTI; K K SRIVASTAVA (UNITED STATES ELSEVIER, 2021)
The book investigates the balance between economic progress and ecological preservation, arguing that sustainable development requires the integration of environmental, social, and economic goals. It emphasizes that unchecked economic growth, driven by modern capitalism and consumerism, is the main cause of global environmental decline, depletion of natural resources, and climate change.
ENGINEERING AND TECHNOLOGY
Keywords: ENVIRONEMENTAL STUDIES; CIVIL ENGINEERING